Estado de conservación de aceite impregnado en hojuelas que se consumen en el Centro Cívico de la ciudad de Trujillo Octubre - Noviembre 2015 - Minchola Zenozain, Thatiana Jackeline (2015)
In this research it determined the "Condition of oil impregnated chips consumed in the Civic Center of the city of Trujillo September-October 2015". 36 samples Musa pardisiaca L (banana) and 36 sample of Ipomoea batatas (sweet potato), for which the measurement index Oxidisability made is used, results exceed the permissible value (3-4) of this analysis concludes that whole of the analyzed samples are not suitable for human consumption